2003
DOI: 10.1002/bdrb.10046
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal window of susceptibility to perfluorooctane sulfonate‐induced neonatal mortality in the Sprague‐Dawley rat

Abstract: The critical period for increased neonatal mortality induced by perfluorooctane sulfonate (PFOS) exposure was evaluated in the rat. Timed-pregnant Sprague-Dawley rats were treated by oral gavage with 25 mg/kg/d PFOS/K(+) on four consecutive days (gestation days (GD) 2-5, 6-9, 10-13, 14-17, or 17-20) or with 0, 25, or 50 mg/kg/d PFOS/K(+) on GD 19-20. Controls received vehicle (10 ml/kg 0.5% Tween-20) on these days. Maternal weight gain was reduced in treated animals during dosing, as were food and water consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 32 publications
(30 reference statements)
6
91
0
2
Order By: Relevance
“…A similar linear decrease of the main phase transition temperature and an increase of peak width have been observed for mixtures of DPPC with increasing mole fraction of several sodium alkylsulfates (C [8][9][10][11][12] ), surfactants which have a headgroup similar to the PFOS potassium salt [21]. These changes in the phase behavior of DPPC-sodium alkylsulfate systems depended only on the concentration of the alkylsulfate surfactant but not on its chain length.…”
Section: Differential Scanning Calorimetry Studiessupporting
confidence: 70%
See 3 more Smart Citations
“…A similar linear decrease of the main phase transition temperature and an increase of peak width have been observed for mixtures of DPPC with increasing mole fraction of several sodium alkylsulfates (C [8][9][10][11][12] ), surfactants which have a headgroup similar to the PFOS potassium salt [21]. These changes in the phase behavior of DPPC-sodium alkylsulfate systems depended only on the concentration of the alkylsulfate surfactant but not on its chain length.…”
Section: Differential Scanning Calorimetry Studiessupporting
confidence: 70%
“…For example, this direct impairment of pulmonary surfactant may be a contributing factor in the impaired lung function reported in postnatal animal studies and at least partly explain the neonatal mortality observed in these studies [9,10]. Further studies are therefore warranted to fully understand the direct effect of PFOS on structure and function of biological lipid assemblies, especially pulmonary surfactant.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This compound has been revealed to posses undesirable toxic characteristics such as weight loss, hepatocellular hypertrophy and lipid vacuolation, reduction of serum cholesterol and thyroid hormones, increase in neonatal mortality, and disturbance of neuroendocrine. [16][17][18][19] On the other hand, 8-2 fluorotelomer alcohol is widely utilized, and the global production of 8-2 fluorotelomer alcohol is estimated to be 5ϫ10 6 kg/year during the period 2000-2002. 20) This may make one suppose the increase in the risk of human exposure to this chemical.…”
mentioning
confidence: 99%